Financial inclusion in MSME: the role of technology adoption and digital economy - Ce Gunawan; Bambang Somantri (FORUM EKONOMI, 2023)
This study aims to determine the effect of the digital economy on the financial inclusion of MSME and try to examine the technology adoption variable in mediating the impact of the digital economy on the financial inclusion of MSME. A conceptual framework was developed and hypotheses were tested through a survey conducted on 100 MSMEs in Sukabumi. Data was collected through a structured questionnaire and was subjected to confirmatory factor analysis. Structural equation modeling (second-order) was used to validate the measurement model and to test the mediating effect. The measurement model is a confirmatory factor analysis and measures the reliability of the observed variables in relation to the latent constructs and indices shows the overall model fit. Structural model results indicate a mediation and a reflective impact  of the extended technology acceptance model on digital economy and financial inclusion relationship. The role of the digital economy and technological adaptation has significant implications for financial inclusion. The digital economy is a sign of future economic development and growth which is marked by the rapid development of business transactions. The world's economies have harnessed the potential of technology-based inclusion through a combination of financial products and services. Technology adoption plays a role in reducing the digital economy gap towards financial inclusion in Sukabumi MSMEs. This study proposes the concept of the digital economy as an independent variable and technology adoption as a mediating variable on the financial inclusion of MSME actors. This research is empirical and has a wider application.